Strategi Pembelajaran Anak Usia Dini di PAUD Yasin AlSys - Yuliartina, Emy (Lembaga Yasin AlSys, 2021)
Early Childhood Education which is then abbreviated as PAUD is one of the educational institutions that is now a concern among the world of education. So that it has become a necessity for observers and education policy makers to pay attention and think about what strategies are best to apply in the implementation of learning in PAUD institutions. PAUD is a coaching effort aimed at children from birth to children aged six years which is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness to enter further education. Learning strategies for early childhood always prioritize aspects of playing, singing (happy), and working in the sense of being active. Playing, singing and doing activities are three characteristics of PAUD. In the learning strategy contains various alternatives that must be considered to be selected in the context of teaching planning. To implement a certain strategy, a set of teaching methods is needed. A teaching program that has been organized by the teacher in every face to face, can be done with various methods. The whole method includes educational media used to describe teaching strategies.